Professional English in Use Law - Brown, Gillian D (Cambridge University Press, 2007)
Professional English in Use Law is suitable for upper-intermediate to advanced students and contains 45 units covering a wide variety of legal vocabulary. Topics include corporate and commercial law, liability, contract law and intellectual property. The book also introduces general legal vocabulary related to legal systems, the legal professions and the skills lawyers need in their daily working lives. Professional English in Use Law is also an ideal companion for learners preparing for the new Cambridge International Legal English Certificate (ILEC) and covers key topics and vocabulary from the exam.